The Method to Strengthen and Innovate the Thinking of Enterprise Economic Management - Niu, Yanhong (Journal of Theory and Practice of Management Science, 2023)
The survival and development of enterprises cannot be separated from scientific and effective management, especially in the current environment of socialist market economy, the competition between enterprises is increasingly fierce and cruel, enterprises to get more long-term development, must keep pace with The Times, reform and innovation, and constantly improve their own economic management level, through continuous strengthening of economic management work, improve and optimize the economic management of enterprises Mode, in order to effectively enhance the competitiveness of enterprises, provide fundamental guarantee for the sustainable development of enterprises, so as to promote the economic benefits of enterprises.